Hasil Inkompatibel pada Pemeriksaan Uji Silang Serasi - Nur Fajrin Aljannah; Francisca Romana Sri Supadmi (Poltekkes Kemenkes Semarang, 2021)
Compatibility testing before blood transfusion is very crucial. This procedure to prevent transfusion reactions due to blood group incompatibility or irregular antibodies. Cross-matching to ensure that the blood safe for the recipient. There are two results in the cross-matching, namely compatible and incompatible. This study aims to determine the inappropriate results of cross-matching at Blood Transfusion Service of the Indonesian Red Cross, Kulon Progo Regency. This study used a quantitative descriptive research design with a retrospective approach. The samples used in this study were 78 incompatible samples in Blood Transfusion Service of the Indonesian Red Cross, Kulon Progo Regency. The sampling technique used was the total population. Methods of data analysis using descriptive analysis. The results show incompatibilities of most compatible cross tests found in minor and auto control (96.1%) with male gender frequency (35.9%) and women (64.1%). The most blood type that has incompatibilities is blood type O (43.3%). The most Diagnosis is anemia (76.9%), and the most components are PRC (88.4%). The most incompatible types are minor and auto control and the most commonly encountered in women, O blood type, anemia, and components of PRC.